Polyphenolic metabolites in Scutellaria baicalensis as potential candidate agents for the treatment of ischemic stroke - Zhang, Jinlong; Li, Songzhe; Huang, Lina; Jiang, Xicheng (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to elucidate the therapeutic effects of polyphenolic metabolites from Scutellaria baicalensis Georgi against ischemic stroke. The findings are expected to provide experimental evidence and novel insights to guide the future development of these metabolites.Materials and methodsThis review was conducted based on a comprehensive literature search of the PubMed, NCBI, and Google Scholar databases from their inception until August 2025. Key search terms included “Scutellaria baicalensis”, “Scutellaria baicalensis and polyphenols,” “Ischemic stroke,” “cerebral infarction,” “cerebral ischemia-reperfusion injury,” and “toxicity.” The article first summarizes the polyphenolic metabolites of S. baicalensis, such as baicalein, baicalin, wogonin, wogonoside, scutellarin, chrysin, apigenin, chlorogenic acid, and ferulic acid, and provides an overview of the pathophysiological mechanisms of ischemic stroke. The primary focus lies on elucidating the pharmacological mechanisms, potential toxic effects, and strategies for improving the bioavailability of these polyphenols in the treatment of ischemic stroke.ResultsThe polyphenolic metabolites of S. baicalensis significantly alleviate ischemic brain injury through multiple pharmacological mechanisms, including anti-inflammatory, antioxidant, and anti-apoptotic effects, as well as regulation of neurotransmitters, maintenance of the blood-brain barrier, and inhibition of ferroptosis, thereby demonstrating promising neuroprotective potential. Furthermore, although nanodelivery systems can effectively enhance the brain bioavailability of these metabolites, their dose-dependent toxicity requires careful attention.ConclusionThe polyphenolic metabolites of S. baicalensis exhibit promising development prospects due to their synergistic therapeutic effects on ischemic stroke via multi-targets and multi-pathways. To advance these metabolites toward clinical application, a strategic focus on the optimization of delivery systems and comprehensive safety assessment is imperative.